Influence of Indonesia in the Early Nationalist Movement in Sabah, Malaysia: A Case Study of Barisan Pemuda Organisation (BARIP) (1946-1948) - Eko Prayitno Joko; Ali Maksum; Ramli Dollah; Md. Saffie Abdul Rahim; Zaini Othman; Adi Jafar (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
The development of nationalism in Malaysian society is one of the important aspects that is frequently explored by social and humanities scientists. However, the debate on this matter is more focused on Malaya and Sarawak, causing the documentation on the development of nationalism among the people of Sabah to still be far from what’s expected. This situation indirectly influenced the meaning of the writings of Western scholars who stated that Sabah is a “state without politics” before and after the early years of World War ll. Whereas, the development of nationalism among the people is also not much different from the national consciousness in both the regions centered on Indonesia. Even so, the effort to trace this linkage is not given enough attention that it is possible the influence of Indonesia in raising the nationalism spirit of the Sabah people is not known by the general public. Therefore, this writing aims to reveal the development of nationalism in Sabah which was also directly driven by Indonesian figures in Sabah based on the emergence of Barisan Pemuda (BARIP). This effort was highlighted by elevating the role of Indonesian figures in mobilising BARIP as one of the political organisations that fought for independence from the British since they had earlier been exposed to the disadvantages of imperialism and colonialism. The data collection of this article was conducted through interviews with several proto witnesses who were either directly involved or saw the BARIP radical movement. The authors also conducted library studies by collecting intelligence reports in the National Archives and Zakaria Gunn’s private collection in the form of personal letters. With that later, this writing is not only able to offer a new dimension in understanding the nationalism development of Sabah society but also puts the position of Indonesian figures at sensible places in the historiography of Sabah politics.